Možnosti uporabe trajnega srčnega spodbujevalnika pri paroksizmih atrijske fibrilacije - Kamenik, Borut (Zdravniški vestnik, 2005)
Background. Prevention of atrial fibrillation is a big therapeutic challenge because of all known negative consequences of this the most frequent cardiac arrhythmia. Numerous of clinical studies showed bad control or ineffectiveness of antiarhythmic drugs. Nonfarmakological therapies like surgical treatment, radiofrequency ablation and atrial pacing are being tested. Effectiveness of atrial pacing in prevention of paroxysmal artial fibrillation has been documented in numerous prospective studies and is effective for a long time interval, but only for patients with bradicardic underlying cardiac rhythm. In Normocardic rhythm or normal AV conduction the effective Atrial fibrillation prevention was not proven. The mechanism of action is based on premature atrial complex suppression, reduction of dispersion of refractoriness after short-long cycles and reduction of interatrial conduction delay. The atrial stimulation site or multi-site atrial pacing could be effective in AF prevention when interatrial conduction delay is present; otherwise the difference is not significant. Conclusions. In bradicardic patient who has frequent paroxysms of atrial fibrillation, regardless if bradycardia is due to ineffective antiarrhythmic drug treathement, implantation of DDDR pacemaker with atrial prevention algorhythm is indicated. If the P-wave duration is >120 milliseconds multi-site atrial pacing or septal atrial pacing should be considered. Pacemaker diagnostic tools could be used for adequate start of anticoagulant therapy and control of effectiveness of anthyarhythmic drug therapy.
Keywords: Atrial fibrillation; Atrijska fibrilacija; Electrostimulation; Elektrostimulacija; Heart; Pacemaker; Srce; Srčni spodbujevalnik